Mother’s Knowledge of Expiration Dates, Beyond-Use Date (BUD), and Storage Conditions for Compounding and Non-Compounding Drugs - Isnenia; Siti Julaiha (Jurnal Kefarmasian Indonesia, 2024)
Patients can obtain various pharmaceutical dosage forms, both compounded and non-compounded. The expired date is no longer a benchmark when the patient or pharmacist opens the primary packaging in preparation but uses the Beyond-Used Date (BUD). Beyond-used date (BUD) has a shorter time than the expiration date. Storage conditions in the household play an important role in the quality of the drug and its feasibility for consumption. This study aimed to compare knowledge about the expired date, BUD, and drug condition storage in two groups, compounding and non-compounding. This research was quantitative, with a cross-sectional design. The sample of this study was the mothers of pediatric patients who received outpatient treatment at one of the primary health centers. The sampling technique was carried out purposively. Data were collected through interviews in September-October 2021. The results of this study show that the respondents are predominantly in the range of 26-45 years, senior high school education, status as housewives, and insurance. The level of knowledge of both the non-compounding groups in the three aspects is greater than that of the compounding group. There is a significant difference in the compound and non-compounding groups in the knowledge of expired date (p=0.000) and BUD (p=0.000). There is no significant difference in knowledge of storage conditions (0.347). This study concludes that there is a significant difference in knowledge between the two groups in expired date and BUD, where the compounding group has greater good knowledge.